2017
DOI: 10.30968/rbfhss.2017.083.006
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização Dos Medicamentos Administrados Por Sonda De Nutrição E as Possíveis Interações Fármaconutrição Enteral

Abstract: Introdução: Sondas de nutrição estão sendo cada vez mais empregadas para a administração de medicamentos quando há impossibilidade de ingestão oral. Seu uso pode resultar em potenciais complicações como obstrução da sonda, redução da eficácia do fármaco, aumento de efeitos adversos e a incompatibilidade de fármacos com os componentes da dieta enteral. Objetivos: Categorizar os medicamentos prescritos via sonda de nutrição buscando possíveis interações entre os fármacos e a dieta enteral de pacientes hospitaliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…13 This common result in several studies on the subject matter can be due to the fact that cardiovascular diseases represent the third cause of hospitalization and also to the prevalence of hypertensive patients in the country, corroborating what was found in this study. 14,15…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…13 This common result in several studies on the subject matter can be due to the fact that cardiovascular diseases represent the third cause of hospitalization and also to the prevalence of hypertensive patients in the country, corroborating what was found in this study. 14,15…”
Section: Resultsmentioning
confidence: 99%
“…3 In this way, the pharmacist ceases to be only a technical holder of knowledge and starts to act in the clinical practice integrated to the team as a reference for the pharmacotherapeutic needs. 3,14,15,22 This study showed the importance of the performance of the clinical pharmacist in the guidance of the multi-professional team in patients who are using an enteral catheters, and the articulation of this team in face of each particularity when it is necessary to use medication via this route, aiming at the quality of care provided to the patient.…”
Section: Route Exchangementioning
confidence: 96%
See 1 more Smart Citation